The state of the art in the conservation and management of small ruminant genetic resources: The sub-Saharan Africa perspective - Lebbie, S.H.B.; Ramsay, K. (Seoul National University, 1998)
Small ruminant genetic resources (SRGR) in sub-Saharan Africa (SSA) play an important role in the welfare of the people, especially the resource poor. SSA is endowed with a diverse SRGR maintained under equally diverse and complex production systems. The public and the private sectors are key factors involved in the conservation and management of SRGR in SSA but with the latter playing a dominant role. Currently the emphasis is on in-situ rather than ex-situ conservation and management. In order to make SRGR conservation attractive and sustainable, the strategy must be associated with some economic benefits. This could be achieved by commercialising SRGR by adding value to them, particularly the indigenous varieties. There is also need to promote conservation awareness and build capacity among the stakeholders through research, extension and training. Policy changes and political as well as financial commitment are needed at both national and regional levels to implement these actions. Inter- and intra-regional co-operation is necessary to succesfully accomplish these actions.